Clinical efficacy of bone marrow mesenchymal stem cells in chronic spinal cord injury: A single-arm meta-analysis of clinical trials - Dewa Putu Wisnu Wardhana; Cindy Thiovany Soetomo; Agung Bagus Sista Satyarsa; Sri Maliawan; Tjokorda Gde Bagus Mahadewa (Physical Therapy Journal of Indonesia, 2025)
Background: Chronic spinal cord injury (SCI) leads to irreversible neurological deficits with limited therapeutic options, making it a major challenge in neuroregenerative medicine. This study aimed to evaluate the clinical efficacy of bone marrow mesenchymal stem cells (BMMSC) therapy in patients with chronic SCI using a single-arm meta-analysis. Methods: This research was conducted using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, covering studies up to August 2024 in PubMed, CENTRAL, and ScienceDirect. Included trials applied BMMSC therapy in patients ≥1 year post-injury. A random-effects model was employed using R software. Outcomes included changes in the American Spinal Injury Association (ASIA) impairment scale, somatosensory evoked potentials (SSEP), motor evoked potentials (MEP), infralesional voluntary muscle contraction (IVMC), active muscle reinnervation (AMR), and urodynamic parameters. Heterogeneity was assessed with the I² statistic, and study quality was evaluated via ROBINS-I. This study has been registered on PROSPERO with registration number CRD42024577161. Results: Seven studies comprising 133 patients were included. AIS grade improvement was observed in 0.37 (95% CI: 0.24–0.52). Improvements were also seen in SSEP at 0.40 (95% CI: 0.18–0.67), MEP at 0.37 (95% CI: 0.25–0.51), IVMC at 0.47 (95% CI: 0.34–0.60), and AMR at 0.74 (95% CI: 0.39–0.92). Urodynamic outcomes demonstrated increased maximum cystometric capacity [0.48 (95% CI: 0.30–0.67)], improved bladder compliance [0.73 (95% CI: 0.55–0.85)], and reduced detrusor pressure [0.61 (95% CI: 0.43–0.76)]. Conclusion: BMMSC therapy was associated with clinically meaningful neurological and urodynamic improvements in chronic SCI. Standardized administration protocols and randomized controlled trials are necessary to validate efficacy and optimize treatment paradigms.